THE IMPACT OF DIGITAL ADVERTISING ON GENERATION Z CONSUMPTION BEHAVIOR - Pasaribu, Donald Frensius; Irawan, Dimas Ariyoga; Hansyah, Rico Hafis; Khalili, Inda; Silalahi, Christian Slamat; Waruwu, Dewi Permata (Yayasan Amanah Nur Aman, 2025)
This study aims to analyze the impact of digital advertising on the consumption behavior of Generation Z in the era of social media. Generation Z is known as the most adaptive group to technological developments, with consumption patterns strongly influenced by digital media such as Instagram, TikTok, and YouTube. The research uses a qualitative approach with a literature review method by examining previous studies on digital advertising effectiveness, influencer roles, and Gen Z’s consumption patterns. The findings show that digital advertising significantly affects Generation Z’s consumption behavior psychologically, socially, and emotionally. Visually appealing content, influencer marketing strategies, and instant shopping features such as TikTok Shop encourage impulsive and emotional buying. However, the influence of digital advertising not only increases sales but also shapes self-image and social identity in digital spaces. The study highlights the importance of ethical, creative, and youth-aligned digital communication strategies to build sustainable brand relationships.